EVALUASI KINERJA PROGRAM REHABILITASI RUMAH TIDAK LAYAK HUNI DI KABUPATEN PURBALINGGA - Pramitha, Putri Prissilia; Warsono, Hardi (Journal of Public Policy and Management Review, 2016)
This study was prepared for evaluating program performance of Unliveable Rehabilitation Home Program in Purbalingga using indicators based on AKIP which are the input, output, outome, benefit and impact. As in this program there are gaps or constraints that may affect the results of program performance of Unliveable Rehabilitation Home Program in Purbalingga derived from the input, output, outcome, benefit, and impact The results obtained are that the human resources lacking in terms of quantity, although the existing human resources are appropriate and optimal, overall target number of uninhabitable houses in the district Purbalinga are 27.533 homes, but new in rehab just 100 houses in accordance with appropriate housing ie roof pedestal and wall, this program can not be said to alleviate poverty, overall, the benefits are felt only to the 100 beneficiaries of rehabilitation home, this assistance has not been felt for alleviating poverty because the aid was stimulated and only include one measure, namely board. So, we may conclude that the performance of unliveable rehabilitation home program in Purbalinggawas good, based on the gains that have been achieved. This program was not the final solution to overcome poverty because it only resolve section of the board. Advice can be given by researcher are that the implementation of the program conducted during dry season, helping each other when collecting document, creating more leaders in society or making certain committee to do implementation on the field outside of the instrument.